Analisis Pemahaman UMKM di Kota Semarang terhadap Kebijakan Produk Halal - Widayat, Widayat; Suzery, Meiny; Ardianto, Hendra Try (Badan Riset dan Inovasi Daerah Kota Semarang, 2022)
The COVID-19 pandemic has had a significant economic impact. The second Sustainable Development Goals are eliminating hunger, achieving food security and good nutrition. The Government of Indonesia has carried out and implemented Law Number 33 of 2014 concerning Guarantees for Halal Products, since 2019. Indonesia is targeting to become the Center for Halal Food Products in the world in 2024. Micro, Small and Medium Enterprises (MSMEs) have a very important role in the Indonesian economy given their great potential in increasing public welfare. The number of MSMEs in Indonesia reached 64.2 million with a contribution to the gross domestic product (GDP) of 61.07% or 8,573.89 trillion. MSMEs are able to absorb 97% of the total workforce and are able to collect up to 60.42% of total investment in Indonesia. To achieve the government's target to become the center of world halal products and continue to contribute to the Indonesian economy, MSMEs have problems in terms of halal certification. This requires intensive study. The Semarang City Government already has Regional Regulation Number 1 of 2021 concerning halal food products. Local governments have an obligation to protect the public from consuming food and beverages that are not guaranteed to be halal. This research is a qualitative research where the respondents used are MSME actors spread across the city of Semarang. The number of MSMEs in Seamarang City until March 2022 was recorded at 23,984 business actors. This study aims to identify problems related to halal certification for MSMEs, understanding, willingness and increasing understanding and willingness in halal certification. The results the profile of MSMEs in Semarang City is Micro Industry and do not have Business License Codes /Nomor Ijin Berusaha (NIB). The MSMEs do not understand about policy Halal Certificate Product about 84%. They don’t also understand about SIHALAL and self-declare / Sertifikasi Halal Gratis respectively 90% and 72%.